A cognitive-behavioural programme for the management of low back pain in primary care: a description and justification of the intervention used in the Back Skills Training Trial (BeST; ISRCTN 54717854). - Hansen, Z; Daykin, A; Lamb, S (2010)
A multicentre randomised controlled trial has been commissioned to evaluate cognitive-behavioural (CB) approaches in the management of subacute and chronic low back pain in primary care. This paper describes the development of the CB intervention based on best-available evidence. Several methods were used to design the intervention. Risk factors for the development of chronic low back pain were identified from the literature to provide targets for treatment, essential components of a CB intervention were considered using the CB treatment model, and the optimal delivery method was used to balance clinical effectiveness and cost-effectiveness within primary care.